Problems of expressing the religious Institute charism in its own law - SZEWCZUL, BOŻENA (Prawo Kanoniczne, 2017)
Present revision of the own law in the Institutes of consecrated life is associated with certain diculty. It is the theological and legal expression of charism in accordance with the intentions of the Founders, in order to save the identity of the Communions founded by them, in spite of the social, economic, and cultural life changes in the course of time. That’s why – in the first place – the article explained the very idea of cha- rism, and shown the problem of diversity of the Holy Spirit gis related to it, such as Founder’s charism, charism of the Institute foundation, Institute charism, and founding charism. Further on in the article, they presented the idea of the spiritual herritage (patrimonium) of the Institute, and its relation to Institute’s charisms.e ve component elements of Institute herritage were described, which are very useful during the constitution renewal, e.g. nature of Institute, its character, purpose, spirit and sound traditions.ey also presented the necessity of expressing the charisms and patrimonium in all areas of the Institute life, and their own rules of laws, which regulate them.